# algebra

sqr root of 3a + 9(sqr root of 27a^3)

1. √27a^3 = 3a√3a
so
√(3a) + 9√(27a^3)
= √(3a) + 27a√(3a)
= √(3a)( 1 + 27a)

not much gained here, poor question if the instructions were to "simplify"

posted by Reiny

## Similar Questions

1. ### Geometry

Find the area of a hexagon with the indicated apothem: 6 sqr root 3 108 sqr root 3 in.^2 432 sqr root 3 in.^2 96 sqr root 3 in.^2 216 sqr root 3 in.^2 Last question, don't know. Please help? Thanks
2. ### Algebra2/Trig

sqr(x^2-4)+(x^2)/x^2+1 I got ((x^2+1)*sqr(x^2-4)+x^2)/x^2+1 But my teacher gave (sqr(x^2-4)+x^2)/x^2+1 I did the problem over again but I can't figure out why my teacher got the answer. Can someone confirm that my teacher is right
3. ### Algebra 2

Ok, so I'm trying to find the inverse of each function. We're learning about Inverse Functions and Relations. The problem is f(x)=sqr.root of x/6 The sqr root is confusing me.
4. ### Calc

How close is the semi circle y= sqr.root of 16-x^2 to the point (1, sqr.root 3)? using Optimization
5. ### Math

Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My Answer: sqr(x+1)/sqr( x-1) sqr(x^2-1)/ (x-1) However, I also have to state the restrictions to the domain and range, which I do not know how to do. Could
6. ### Math

Find the quotient function f/g for f(x)=sqr(x+1) and g(x)= sqr( x-1). My Answer: sqr(x+1)/sqr( x-1) sqr(x^2-1)/ (x-1) However, I also have to state the restrictions to the domain and range, which I do not know how to do. Could
7. ### algebra

(sqr root of 2 + 3*sqr root of 5)(sqr root of 2-3*sqr root of 5)
8. ### Algebra

For what values does the sqr root of 2x = x square root 2 ?
9. ### math

I have a question I have been working on since yesterday and I am not making this up. I couldn't get the right answer. If sin theta = -2/3, which of the following are possible? A: cos theta= -the sqr rt of 5/3 and tan theta =2/3.
10. ### calculus

Is this the correct answers for these questions Verify the means value theorem holds on the interval shown. Then, find the value c such that f'(c)=(f(b)-f(a))/(b-a) b.f(x)=x^3=x-4 on [-2,3] c= square root 7/3 c. f(x)= x^3 on

More Similar Questions